Geometry of contact during tooling tasks via dynamic estimation - Phan, Gia-Hoang (2020)
Contact area and contact forces between tool and workpiece are important variables for the estimation of the material removal rate during mechanical polishing, carried out during either manual or robotic operations. With a view to estimate the contact conditions during tool-workpiece interaction, a conceptual framework to capture human performance in terms of kinematics and interaction dynamics between a hand-held power tool and a workpiece is presented in this paper. In particular, a hand-held power tool was instrumented to measure 3D kinematics and 3D interaction dynamics (e.g., 3D forces and torques) during manual finishing operations. Algorithms from the literature were adapted to sense dynamically (e.g., based on force/torque measurements) the point of contact between a hard mounting-bit and the workpiece. Based on this estimation, from the shape of the mounting-bit, we estimated important geometric features. A first-order analysis allows splitting contact forces into normal force and friction components. The contact point along the mounting-bit surface determines the actual relative velocity at contact and, with friction, the mechanical power involved in the finishing process. A second-order analysis at contact point provides information about the curvature of the mounting-bit and the workpiece at contact. Experimental results show that the contact point between the tool and the workpiece can be precisely estimated, as validated using 3D motion capture. First- and second-order geometric features have been extracted from experimental data and compared with optical scans. A geometric curvature at contact can be used in material removal rate models, although actual estimation of material removal is beyond the scope of this work. The results of the study are promising and based on data derived from manual operations; the proposed algorithms can be readily applied to robotic applications and used to facilitate tool path programming.